Willed to wed him - Crews, Caitlin (Harlequin presents, 2022)
"To save her family legacy, Annika Schuyler must tie herself to the one man who infuriates her most. But though she knows intimidating Ranieri Furlan is marrying her in cold blood, he ignites a fire in her she never dreamed possible... CEO Ranieri will fulfill his mentor's dying wish, but no matter how much he desires innocent Annika, he can never love her. Yet behind the doors of his Manhattan penthouse, their convenient marriage becomes something more. Something that threatens to melt even this billionaire's frozen heart!" -- Page [4] cover.